2022
DOI: 10.1039/d2qm00742h
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring 1T/2H MoS2 nanosheets on carbon nanofibers containing Si nanoparticles as a flexible anode for lithium–ion batteries

Abstract: Silicon-based (Si) materials have received exceptional attention as the most promising fall-back option for lithium-ion batteries (LIBs) due to their high specific capacity. Regrettably, the huge volume variation, inferior intrinsic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…As expected, the biomimetic AGO−Si/C electrode, under various mass loading of 1.6, 2.9, 3.5 and 4.1 mg cm −2 , can deliver the impressive areal-capacity of 3.5, 6.9, 7.4, and 10.0 mAh cm −2 , respectively (Figure 4b). It should be noticed that the maximum areal−capacity of biomimetic AGO−Si/C electrode is markedly superior to previous reported Si-based anodes [41][42][43][44][45][46][47][48][49][50][51][52] (Figure 4c; Table S1, Supporting Information). Due to the fast electron/ion migration within 3Dinterweaved carbon architecture, the AGO−Si/C electrode delivers high areal-capacities of 2.2, 2, 1.5, and 1.1 mAh cm −2 under different areal current densities of 0.25, 0.5, 1.25, and 2.5 mA cm −2 , respectively (Figure 4d; Figure S10a, Supporting Information).…”
Section: Electrochemical Performancementioning
confidence: 61%
“…As expected, the biomimetic AGO−Si/C electrode, under various mass loading of 1.6, 2.9, 3.5 and 4.1 mg cm −2 , can deliver the impressive areal-capacity of 3.5, 6.9, 7.4, and 10.0 mAh cm −2 , respectively (Figure 4b). It should be noticed that the maximum areal−capacity of biomimetic AGO−Si/C electrode is markedly superior to previous reported Si-based anodes [41][42][43][44][45][46][47][48][49][50][51][52] (Figure 4c; Table S1, Supporting Information). Due to the fast electron/ion migration within 3Dinterweaved carbon architecture, the AGO−Si/C electrode delivers high areal-capacities of 2.2, 2, 1.5, and 1.1 mAh cm −2 under different areal current densities of 0.25, 0.5, 1.25, and 2.5 mA cm −2 , respectively (Figure 4d; Figure S10a, Supporting Information).…”
Section: Electrochemical Performancementioning
confidence: 61%
“…The C 1s spectrum could be divided into three peaks at 284.8, 286, and 288.6 eV, assigned to the C–C, C–O, and CO bond, respectively, indicating that the carbon source was encapsulated well on the SiO x particles after the pyrolysis process (Figure c). , The O 1s spectrum could be decomposed into the Co–O bond, Si–O bond, C–O bond, and CO bond (Figure d), and the metal Co–O bond further revealed that the metal oxide CoO was fabricated successfully. The Si 2p spectrum could be deconvoluted into Si 1+ , Si 2+ , Si 3+ , and Si 4+ in SiO x (Figure e). , As it is seen from the Co 2p high-resolution XPS spectra (Figure f), the two peaks at 780.2 and 796.2 eV were associated with Co 2p 3/2 and Co 2p 1/2 and the two peaks at 786.6 and 802.2 eV belonged to the satellite peaks of Co 2p 3/2 and Co 2p 1/2 , respectively. The above experimental results could fully demonstrate that the porous structure of the SiO x @C@CoO composite was obtained.…”
Section: Results and Discussionmentioning
confidence: 84%
“…The Si 2p spectrum could be deconvoluted into Si 1+ , Si 2+ , Si 3+ , and Si 4+ in SiO x (Figure 3e). 40,41 As it is seen from the Co 2p high-resolution XPS spectra (Figure 3f), the two peaks at 780.2 and 796.2 eV were associated with Co 2p 3/2 and Co 2p 1/2 and the two peaks at 786.6 and 802.2 eV belonged to the satellite peaks of Co 2p 3/2 and Co 2p 1/2 , respectively. The above experimental results could fully demonstrate that the porous structure of the SiO x @C@CoO composite was obtained.…”
Section: Resultsmentioning
confidence: 85%
“…Du et al [30] demonstrated that the Si@CNF@1T/2H MoS2 electrode shows promising potential for flexible and free-standing anode materials for LIBs, exhibiting good rate capability, cycle performance, and a high initial coulombic efficiency (ICE) of 94.5%. Shu et al [31] confirmed the lithiated MoS2 phase change through DFT and ab initio molecular dynamics (AIMD) simulations.…”
Section: Introductionmentioning
confidence: 99%